Characteristics of vacuum-packed sheep meat stored under fluorescent light - Vieira, Natalia Carolina [UNESP]; Andrighetto, Cristiana [UNESP]; Souza, Érica Pereira [UNESP]; da Luz Zanetti, Patrícia Aparecida; Maestá, Sirlei Aparecida [UNESP]; Ricardo, Hélio Almeida [UNESP]; da Fonseca, Ricardo [UNESP] (My University, 2023)
This study aimed to evaluate the possible variations of physicochemical and microbiological characteristics of frozen sheep meat, vacuum-packed under fluorescent light exposure at different storage times. Sixteen Longissimus lumborum muscles from male Ile de France lambs were collected for meat quality analyses of pH, color, shear force, weight loss due to cooking, water holding capacity, lipid oxidation, mesophilic and psychrotrophic microorganisms, and enterobacteria. The samples were randomly identified and stored in a horizontal freezer under the incidence of fluorescent light (IL) and no incidence of light (NL) for 30 and 60 days plus the control treatment (day 0). An interaction was observed between treatments for pH and water holding capacity (p<0.05), with superior results for IL-30 and NL-60, respectively. However, the other variables showed differences only regarding the main effects, mainly in terms of time (p<0.05). The contents of L∗, a∗ and b∗, C∗, O/M, weight loss due to cooking, and lipid oxidation increased as the meat was stored longer (p<0.05). The shear force did not differ between treatments (p>0.05). Meat microbiological quality was not affected by the lightness factor, except for enterobacteria (p<0.05), in which the IL treatment had lower counts of these microorganisms. Therefore, the physicochemical and microbiological characteristics were not affected by the incidence of light. However, the meat undergoes changes as the storage time under freezing increases.
Keywords: Color; Lambs; Lighting condition; Lipid oxidation; Microbiology; Shelf life